Perceptions about memory reliability and honesty for children of 3 to 18 years old - Wright, Daniel B. (Legal and criminological psychology, 2010)
Purpose. To examine the relationship between perceived memory characteristics and age. Method. Participants rated the reliability and honesty of children's memory for one of two events. The children's ages varied from 3- to 18-years-old. Results. Participants (N = 612) believed that memory reliability increased with age, but the observed effect was non-linear. Perceived reliability increased rapidly for children from 3 to 6 years. After this, male participants believed memory reliability increased, but less than in early childhood. Female participants did not think memory reliability increased in middle childhood and adolescence. Further effects involving type of event, age of participant, and the gender of the eyewitness were observed for honesty and the relationship between these attributes and beliefs in guilt. Conclusions. These findings stress the need for more research on development trends of memory in middle childhood and adolescence.